Do location and legal status matter in microfinance institutions' performance? Evidence from sub-Saharan Africa. Issue 3 (3rd April 2021) - Tehulu, Tilahun Aemiro
ABSTRACT: This article examines the effects of location and legal status on the performance of microfinance institutions (MFIs) within sub-Saharan Africa (SSA) using panel dataset of 138 MFIs in 31 SSA countries covering 2004 to 2014. The econometric results show that legal status and location significantly influence the capitalisation, portfolio quality, profitability, liquidity, and deposit mobilisation of MFIs. MFI credit growth and deposit growth are similar across locations, but significantly differ by legal status. Most importantly, we found new evidence that location has moderating effect on the legal status–performance nexus of MFIs within SSA.